2016
DOI: 10.1016/j.jceh.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Balloon-Occluded Retrograde Transvenous Obliteration (BRTO): A Novel Method of Control of Bleeding from Post-Glue Ulcer over Gastric Varices. Report of Two Cases and Review of Literature

Abstract: Bleeding gastric varices (GV) are managed by cyanoacrylate glue injection with transjugular intrahepatic portosystemic shunt (TIPSS) as modality for treatment failure. Ulcer can form at the site of glue injection over GV and it can cause bleeding. Treatment approach for such bleed is not well described. Balloon-occluded retrograde transvenous obliteration (BRTO), TIPSS, and devascularization remain the treatment options in this scenario. BRTO is an endovascular procedure where a balloon catheter is inserted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…6). 3,[22][23][24][25] Pooled analysis of the published Indian studies revealed survival rate at 1 year among patients undergoing BRTO of 97% (95% CI: 0.91 to 1.0) and 98% (95% CI:0.89 to 1.0) by fixed and random effect models, respectively (►Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6). 3,[22][23][24][25] Pooled analysis of the published Indian studies revealed survival rate at 1 year among patients undergoing BRTO of 97% (95% CI: 0.91 to 1.0) and 98% (95% CI:0.89 to 1.0) by fixed and random effect models, respectively (►Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…7). 3,[22][23][24][25] To our knowledge, there are two other large studies from the Indian subcontinent, describing the role of BRTO in patients with bleeding GVs or HE. 3,25 The sclerosant used by authors in both these studies was a mixture of air, STS, and lipiodol in a ratio 3:2:1.…”
Section: Discussionmentioning
confidence: 99%